PENGARUH SEMANGAT KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. MANDIRI UTAMA FINANCE SITUBONDO - Karnadi, Karnadi; Pramesthi, Riska Ayu; Nise’, Ahmad (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of the study was to determine the effect of work morale and work ability on employee performance with job satisfaction as an intervening variable at PT. Mandiri Utama Finance Situbondo. The sample in this study were 46 employees of PT. Mandiri Utama Finance Situbondo. The sampling technique was determined by the saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that work enthusiasm has a positive and significant effect on job satisfaction, work ability has a positive and significant effect on job satisfaction, work spirit has a positive and significant effect on employee performance, work ability has a positive but not significant effect on employee performance, job satisfaction has a negative but significant effect on employee performance, work morale has a negative but significant effect on employee performance through job satisfaction, work ability has a negative and insignificant effect on employee performance through job satisfaction